An Ecocritical Reading of Syed Manzoorul Islam2019;s Novel Shakuner Dana (Global Journal of Human-Social Science, 2022)
Like other countries across the globe Bangladesh is also experiencing an environmental turn in literature Eco-fiction and climate fiction are the new avatars of contemporary literature with a particular focus on ecological concerns This kind of literature is on the rise as the world grapples with climate emergency a new entry in Oxford Dictionaries The governing theme and subject-matter of such literature pertain to the environment which has encountered severe challenges causing a massive threat to the existence of humans and non-humans alike In addition the eco-focused literature highlights the degradation of biodiversity at local and global levels Similarly environmental pollution is a common feature of almost any global discourse including literary studies Besides global warming is a buzzword occupying a huge space in academic discussions As a branch of humanities literature responds to such phenomena through evocative storytelling informed by scientific facts and suggestions The latest theoretical school namely ecocriticism studies the environment in all its manifestations and nuances available as an active and evocative force in literature
Keywords: eco-fiction; environmental degradation; environmental justice; ecocriticism; ecofeminism; Bangladeshi eco-fiction